MASALAH METODOLOGIS ILMU HUKUM INDONESIA - Sebastian, Tanius (Faculty of Law, Parahyangan Catholic University, 2018)
This article is the result of an explorative study on methodological issues in Indonesian legal science. It uses a literature review to trace current debate on three interrelated issues concerning legal scholarship, legal development and legal pluralism. Each of these issues will be juxtaposes to contemporary legal discourse. Separately the issue of legal scholarship will be just apose to the praxis of legal research methodology and legal education; legal development to “law and development” paradigm; legal pluralism to rule of law. The author follows the legal thinking tradition employed by influential legal scholars: Paul Scholten, Soediman Kartohadiprodjo and B. Arief Sidharta. The standing of other prominent legal authors such as Mochtar Kusuma-Atmadja and Soetandyo Wignyosoebroto, to the extent that their ideas are relevant to this article, will be briefly discussed.